Teachers’ Perceptions and Observed Practices of Deep Learning in Elementary School Teaching: A Qualitative Study at Sekolah Dasar Negeri 060971 - Reno Simanullang (Jurnal Pendidikan: Media, Strategi, dan Metode, 2026)
Deep Learning (DL) has increasingly become an important pedagogical orientation in elementary education because it emphasizes meaningful understanding, inquiry, reflection, collaboration, critical thinking, creativity, and real-life learning application. However, the implementation of DL in elementary classrooms depends strongly on teachers’ conceptual understanding, instructional readiness, classroom strategies, leadership support, and the availability of learning resources. This study explores teachers’ perceptions and observed practices of Deep Learning at Sekolah Dasar Negeri 060971. The study employed a qualitative descriptive case study design supported by classroom observation scores. The participants consisted of 20 elementary school teachers, one headmaster, and two vice headmasters. Data were collected through semi-structured teacher interviews, a 15-item classroom observation checklist, and leadership interviews. The interview data were analyzed using thematic analysis, while observation scores were analyzed descriptively using mean scores and categorical interpretation. The findings revealed that teachers understood Deep Learning as meaningful, reflective, student-centered, inquiry-oriented, and conceptually deep learning rather than memorization-based instruction. Teachers perceived DL as important for developing students’ critical thinking, engagement, independence, collaboration, creativity, responsibility, and real-life understanding. Observation data showed that DL practices were highly observed overall, with an average score of 3.68 out of 4.00. The strongest observed indicators were effective classroom management, active student engagement, critical thinking encouragement, and constructive feedback, while technology integration and student reflection were comparatively lower, although still categorized as highly observed. Leadership interviews confirmed that school leaders supported DL through training, mentoring, supervision, technology integration, and school policies, but challenges remained in time allocation, resources, assessment procedures, curriculum demands, and sustained professional development. The study concludes that Deep Learning at SD Negeri 060971 has been positively perceived and substantially practiced, but its sustainability requires stronger teacher training, clearer assessment guidance, improved technology access, collaborative planning, and continuous school-based professional learning.